The Impact of Global Economic Crisis on the Malaysian Palm Oil Industry - Wo, Chin Yong (2010)
Global economic crisis particularly the recent one started in year 2007, had impacted the global financial system badly seeing financial institutions closing down, which eventually affected the world economy negatively, with countries such as Iceland, falling into bankruptcy. During this global economy downturn, we saw many businesses went into predicament. Although the Malaysian economy was not affected too badly by this global economy crisis, being one of the important pillars of the Malaysian economy, the palm oil industry seemed to have sustained the crisis and performed well. In fact, how much did the global economy crisis impacted on this industry? In this paper, we are going to have an in-depth research and understanding of the palm oil industry as well as the recent credit crunch. We will explore the role and contributions of palm oil industry to the Malaysian economy, and analyse the performance of the Malaysian palm oil sectors during and post-crisis. This paper will then be concluded with some of the challenges identified and need to be resolved in order for the industry to excel further not only in the Malaysian market but also the other palm oil producing countries around the world.